2020
DOI: 10.12659/msm.921775
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 8 as a Prognostic Biomarker of Gastric Cancer: An Analysis of The Cancer Genome Atlas (TCGA) Data

Abstract: Background:Glutathione peroxidase 8 (GPX8) has previously been shown to play a role in Keshan disease. In the present study, we explored the prognostic relevance of GPX8 expression in patients with gastric cancer (GC) based upon The Cancer Genome Atlas (TCGA) data. Material/Methods:We assessed the relationship between the expression of GPX8 and clinicopathological findings in GC patients via logistic regression analyses, Kruskal-Wallis tests, and Wilcoxon signed-rank tests. We further assessed the prognostic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…To study this issue, we detected the expression of GPX8 in gastric cancer and detected the overexpression of GPX8 in gastric cancer tissues and cell lines. This result was consistent with the previous report that revealed the aberrant high level of GPX8 in gastric cancer tissues compared with normal controls based on TCGA database [ 13 ]. Additionally, our study showed that GPX8 overexpression promoted the proliferation, migration and invasion of gastric cancer cells.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…To study this issue, we detected the expression of GPX8 in gastric cancer and detected the overexpression of GPX8 in gastric cancer tissues and cell lines. This result was consistent with the previous report that revealed the aberrant high level of GPX8 in gastric cancer tissues compared with normal controls based on TCGA database [ 13 ]. Additionally, our study showed that GPX8 overexpression promoted the proliferation, migration and invasion of gastric cancer cells.…”
Section: Discussionsupporting
confidence: 94%
“…Zhang et al have analyzed the gastric cancer data in TCGA (the Cancer Genome Atlas) database, found a potential prognostic biomarker- GPX8,and proved the high expression of GPX8 was closely correlated with basal cell carcinoma signaling pathway [ 13 ]. Based on KEGG pathway, Basal cell carcinoma signaling includes the Wnt signaling pathway (Additional file 2 : Figure S1) that is critical for tumorigenesis and development [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations